Analytical Evaluation of College Learning Experiences on Students’Problem-Solving Efficacy among Technical and Scientific Areas - Minh-Quang Duong (International Journal of Evaluation and Research in Education (IJERE), 2012)
Problem-solving is important for students to become effective problem solvers in their profession, and for later career success. This study was conducted to explore how learning experiences affect problem-solving efficacy of Vietnamese college students within technical and scientific areas. The study used a questionnaire survey with 430 students’ technical and scientific areas from three member universities at Vietnam National University of Ho Chi Minh City. Results of this study indicated that students’ problem-solving efficacy was within the range of “average” to “high” response. There existed significant differences of problem-solving efficacy of students among the three universities. Various learning experiences of teaching approach, and learning engagement influenced as significant factors affecting students’ problem-solving efficacy.DOI: http://dx.doi.org/10.11591/ijere.v1i2.1663